2003
DOI: 10.1016/s0014-5793(03)01455-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural characterization of a novel member of the natriuretic family of peptides from the venom of Pseudocerastes persicus

Abstract: A novel peptide, PNP (Pseudocerastes persicus natriuretic peptide), was isolated from the venom of the Iranian viper P. persicus. Amino acid sequencing revealed that the 37-residue peptide belongs to the family of natriuretic peptides. The physiological e¡ects of intra-venously PNP infused into anesthetized rats on urine £ow, sodium excretion and blood pressure were comparable to those of atrial natriuretic peptide (ANP). In PC12 cells that were treated with either PNP, ANP, or C-type natriuretic peptide, PNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…Notably, antiplatelet activities have also been reported in a 37-residue peptide, Pseudocerastes persicus natriuretic peptide (PNP), which was isolated from the venom of the Iranian viper, Pseudocerastes persicus [103]. In addition, Michel et al [104] reported the isolation of two N-terminally truncated forms of CNP from the venom of Trimeresurus flavoviridis (habu snake): Tf-CNP (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and Tf-CNP (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) [104].…”
Section: Dendroaspis Natriuretic Peptide and Other Snake Venomsmentioning
confidence: 99%
“…Notably, antiplatelet activities have also been reported in a 37-residue peptide, Pseudocerastes persicus natriuretic peptide (PNP), which was isolated from the venom of the Iranian viper, Pseudocerastes persicus [103]. In addition, Michel et al [104] reported the isolation of two N-terminally truncated forms of CNP from the venom of Trimeresurus flavoviridis (habu snake): Tf-CNP (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and Tf-CNP (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) [104].…”
Section: Dendroaspis Natriuretic Peptide and Other Snake Venomsmentioning
confidence: 99%
“…By contrast, in flexible peptides 1 H a chemical shifts depend mostly on the nature of the attached sidechain, with the identity of neighbouring residues in the sequence having only small effects. After changes in solution conditions and amino acid composition are taken into account, the 1 H N and 1 H a chemical shifts of ANP ox differ little from those recorded in earlier studies of a hexamutant ANP variant (Fairbrother et al, 1994) and of more obviously random coil homologues including urodilatin, which has a 4 amino acid extension at the N-terminus (Weber et al, 1994), and PNP, a natriuretic peptide found in the venom of the snake Pseudocerastes persicus (Amininasab et al, 2004).…”
Section: Resonance Assignmentsmentioning
confidence: 63%
“…40 The rst reptilian NP was isolated from the venom of the Eastern green mamba (Dendroaspis angusticeps), and was termed Dendroaspis natriuretic peptide (DNP). 44 Subsequently, reptilian NPs were puried from the venoms of Pseudocerastes persicus, 45 Oxyuranus microlepidotus, 46 Crotalus durissus cascavella (¼C. d. terricus), 47 Micrurus corallinus, 48 Bungarus avi-ceps, 49 and Agkistrodon halys blomhoffii (¼Gloydius blomhoffii blomhoffii).…”
Section: Natriuretic Peptidesmentioning
confidence: 99%